Analysis of Extrusion Process Parameters in PLA Filament Production for FFF Technology - Senkerik, Vojtech; Bednarik, Martin; Janostik, Vaclav; Karhankova, Michaela; Mizera, Ales (Manufacturing Technology Journal, 2024)
Additive technologies are becoming a common part of not only prototype production, but also piece or small series production. However, the choice of technology and material plays a key role in the applicability of the manufactured parts. The most widespread type of additive technology is FFF technology, which consists of applying a fused plastic string in single layers. The resulting mechanical properties of parts produced using this technology depend not only on the material and structure selected, but also on the process parameters used in the printing process itself. This study deals with the production of filament from PLA, which is the primary material. The advantage is its environmental degradability after the end of the life cycle of PLA products. However, the resulting properties of the printed parts may depend on the way the filament is prepared and in particular on the melt temperature during filament extrusion. This study investigates the effect of the produced filaments on the quality of printed parts. It has been shown that the filament production technology has a significant effect on the quality of printed parts.
Keywords: Extrusion; Filament; PLA; Additive manufacturing